Copyright and film: the impact of style - Joubert, Josua (Department of Commercial Law, 2023)
The modern landscape of the film industry has facilitated an erosion of originality, in respect of both content and style. With significantly greater emphasis placed on the profitability of blockbuster cinema, the underlying creative process is now characterised largely by a crosspollination of ideas and appropriation of specific stylistic choices. Logically, the first line of defence for the protection of one's ideas will be found in intellectual property law, and when considering the regulation of artistic and literary works, one specifically looks to copyright law. As it currently stands, however, the concept of film ‘style' does not at all factor into the operation of copyright law in South Africa nor does it play a significant role in other jurisdictions – the reason for which will be investigated. It is the goal of this dissertation to illustrate why the lack of attention given to concept of style by intellectual property law results in a failure to address the appropriation of style that occurs in modern filmmaking. Practically speaking, it is currently possible for a film to copy the established style of another director and profit from it without even needing to offer credit to the original creator of that style. This dissertation submits that, where the original film in question is proven to rely on the originality of its style – both critically and monetarily – then the appropriation of this style can lead to an unjust copying of one's work, and that protecting such work through consideration of its style, does not create an undue disturbance in the balance between stifling and promoting creativity. Therefore, there is potentially a gap in the law which can be filled by a suggested guideline, and this guideline may aid courts in incorporating film style into the consideration of a copyright infringement claim.